The dialogical self in psychotherapy - Hermans, H. J. M.; Dimaggio, Giancarlo (Brunner-Routledge, 2004)
This book gathers together psychotherapists from divergent origins to show why they think the concepts of dialogue and intersubjectivity need to be incorporated into the therapeutic process and to explore current thinking in the field.